Development and implementation of a pre-tracheostomy multidisciplinary conference: An initiative to improve patient selection. (July 2022) - Raynor, Tiffany; Marcet-Gonzalez, Jessie; Roy, Kevin; Mahoney, Daniel; Murrell, Diane; Hyle, Laurel; Bedwell, Joshua
Abstract: Objective: To describe our institutional experience in implementing a pre-tracheostomy multidisciplinary conference and assess its effects on patient selection and communication between team members and with families. Methods: Descriptive study and retrospective review of patient outcomes in a period prior to (4/2016-1/2018) and following (2/2018-11/2019) implementation of the conference and conference participant survey. Results: In the 21 months prior to the conference, 53 patients out of 67 consults (79%) went on to have a tracheostomy. After implementation, 96 patients, 42 females and 54 males, between 2 weeks and 22 years of age were discussed. 58 (60%) of patients referred for tracheostomy ultimately underwent surgery. Of those managed without tracheostomy, 16% were extubated, 11% were managed with noninvasive respiratory support, and 13% of families chose to redirect care. There was no difference in time between consultation and surgery (p = 0.9), or post-surgical length of stay after the conference was implemented (p = 0.9). Survey responses were gathered from 34 conference participants. Respondents agreed that the conference was useful in facilitating communication among the care team (91%), promoting understanding of the patient's treatment options (85%), promoting understanding about long-term outcomes and progression of underlying disease process (79%), clarifying risks, benefits, and alternatives of treatment options (82%), and informing discussions with the family (70%). Discussion: Potential benefits of a multidisciplinary pre-tracheostomy conference include improved provider communication and shared decision making between the medical team and family. We found a reduction in the proportion of patients who ultimately underwent tracheostomy as a result of a formal multidisciplinary discussion, but did not find either any delays in care, or reduction in post-operative length of stay. Implications for practice: A multidisciplinary team approach to patient selection can foster communication between team members, identify barriers to discharge and quality care at home, and provide caregivers with information necessary to make an informed decision about their child's care.